INVERSI 2D DATA MAGNETOTELURIK UNTUK MENGETAHUI KEBERADAAN HIDROKARBON DAERAH BULA, MALUKU - Elen Novia Limswipin; Syamsurijal Rasimeng; Karyanto Karyanto; Noor Muhammad Indragiri (Engineering Faculty Universitas Lampung, 2018)
There had been done a regional research which tittle is “2D inversion magnetotelluric data for understanding the hidrocarbon presence in Bula, Maluku”. This study aims to determine the resistivity distribution area of research based on data Magnetotelluric, identifying the presence of hydrocarbons based on the value of the resistivity of the results of 2D inversion of data Magnetotelluric. Methods of data processing done are (i) transform raw data from the time domain into the frequency domain, (ii) reduce noise by robust processing, (iii) process combine, (iv) Selection cross power, (v) inversion 1D and 2D. 2D inversion results is sectional subsurface resistivity distribution, layer having resistivity values 7-16 Ωm along MT1 and MT7 point at a depth of 1000 meters is a clay stone which is indicated as cap rock. Layer with resistivity values 34-120 Ωm, which is between the point MT6 and MT7 at a depth of 1500 meters is indicated as the sandstone reservoir. Based on geologic information and sectional 2D inversion seen their fault based on the resistivity contrast is between the point MT2 and MT3, MT3 and MT4 and MT6 and MT7.